Efektivitas Iklan Produk Sunscreen â€œAzarineâ€ Melalui Akun Tiktok @Dictionarei Terhadap Minat Pembelian - Agus Sholeh Darmawan; Meita Anindya Safitri; Ananda Cheryl (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
The development of the internet has a full impact on aspects of life, especially in business. So that the use of social media in the field of product marketing in the current era is in demand by various business people to attract consumer interest. One of them is the facial care product branded Azarine Sunscreen by utilizing the social media platform, the Tiktok account @dictionarei. This study aims to determine the effectiveness of advertisements for Sunscreen Azarine products through the Tiktok @dictionarei account on purchase intention. This research is quantitative with a survey method. The sampling technique used was purposive sampling technique with a sample of 50 people. The data was obtained by distributing questionnaire links through the Google Form and calculated using the Linkert Scale data score. From the results of data analysis using a simple linear regression model, the results of this study found that there was significant effectiveness in advertising Sunscreen Azarine products through the Tiktok @dictionarei account on purchase intention with a significance value of 53.8%.